The The Influence of Fiscal Policy, Monetary Policy and International Trade on Economic Growth in Indonesia (Literature Reviews) - Elhakim, Luqman Elhakim; Ali, Hapzi (Dinasti Publisher, 2023)
The Literature Review article on the Influence of Fiscal Policy, Monetary Policy and International Trade on Economic Growth in Indonesia is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of public finance science. The way of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The outcomes of this literature review study are: 1) Fiscal Policy influences Economic Growth in Indonesia; 2) Monetary Policy affects Economic Growth in Indonesia; and 3) International Trade has an effect on Economic Growth in Indonesia.